Breaking Traditions: the Imperative of Legalizings LGBTQ+ and Same-Sex Marriage - Sinha, Anju (Indian journal of criminology, 2024)
Marriage as an institution is as old as time itself; it has been passed through cultural, social, and normative tints, which influence how we see it. Civilizations and cultures have existed in a conflicting space when it comes to who should be able to enter a relationship or start a marriage; while ancient Greece did not draw borders between sexes, Assyrian Laws viewed it in condemnation and had punishments in place. A legal union of two people of the same gender is known as a same-sex marriage. In the present day, although there are continuous initiatives to recognize and legalize same-sex marriages, in India, they are still not permitted. "Legalizing same-sex marriage is not only a matter of legal recognition and protection for LGBTQ+ couples but also a powerful step toward promoting social acceptance and reducing discrimination. Advocates and activists continue to fight for marriage equality globally, emphasizing the importance of human rights and empathy for diverse identities." (Anunay, 2023). In the face of evolving societal norms and changing perceptions of human rights, the legalization of LGBTQ+ and same-sex marriage stands as a pivotal step toward equality and social justice. This paper examines the areas where same-sex marriage and transgender rights overlap, going into great detail about the background, legal issues, social effects, and international viewpoints of these two vital LGBTQ+ equality issues. Through an analysis of the distinct challenges and achievements faced by transgender people in the context of marriage equality, this article seeks to illuminate the complex relationships between gender identity, love, and human rights. By carefully examining legislative frameworks, cultural narratives, and advocacy initiatives, it emphasizes how important it is to promote acceptance, dignity, and inclusivity for every person, regardless of gender identity or sexual orientation.